Carbon Footprint Analysis in Hydrogen Production Technology from Coke Oven Gas with Life Cycle Approach: Case Studies for Eight Companies - Xiao Chenjiang; Li Wenqing; Wang Ce (E3S Web of Conferences)
This study constructed a carbon footprint analysis model for hydrogen production technology from coke oven gas (COG), based on eight COG-to-hydrogen companies as case studies. It encompassed the mainstream COG-to-hydrogen production technologies currently in use. The research thoroughly explored carbon footprint accounting methods applicable to China’s COG production pathways, with the system boundary defined from cradle to gate, covering: raw material acquisition, raw material transportation, and the hydrogen production process. The results indicated that the energy allocation method effectively reflected the carbon footprint results for COG-to-hydrogen production, with values ranging from 4.33 to 8.72 kg CO2- eq/kg H2. Some companies had significantly reduced the carbon footprint of hydrogen through the adoption of energy-saving and emission-reduction measures. This study provides a reference for carbon footprint accounting model of hydrogen in China and fills the current data gap in the carbon footprint of COG-based hydrogen processes. It holds significant importance for the construction of a green hydrogen supply chain and energy transition strategy in China.